210 A SYSTEMATIC REVIEW OF LONG-TERM OUTCOME COLLECTION FOLLOWING HIP FRACTURE IN IRELAND FROM 2005 TO 2021. (18th November 2021) - Walsh, M; Cunningham, C; Brent, L; Savin, B; Fitzgerald, M; Blake, C
Abstract: Background: The Irish Hip Fracture Database (IHFD) drives clinical improvements across 16 acute hospitals for over 3, 500 patients annually. The IHFD aims to begin recording long-term outcomes. Past practice in Ireland could inform this activity. This review aims to identify and summarise studies that have collected long-term outcomes following hip fracture in Ireland. Methods: A search of electronic databases (MEDLINE, Embase, Scopus, Web of Science, CINAHL) and grey literature was conducted in July 2021 for articles, abstracts, theses and reports. Search terms related to hip fracture and Ireland. Studies published from 2005–2021 were included if post-hospital discharge data were collected in the Republic of Ireland for patients with hip fracture. Study and patient characteristics, data collection methods and long-term outcomes were extracted. Results: From all sources, 21 articles, 3 theses and 84 abstracts from 18 clinical sites were identified. Numbers of patients with hip fracture ranged from 9 to 2, 483 (median 168) across publications. The most common outcome recorded was mortality (59% of publications), most frequently at 30 days and/or one year. Ascertainment methods for mortality included electronic patient records, online death notices, phone calls to family or general practitioners and the national death register. Non-mortality long-term outcomes were assessed in 64% of publications, most commonly through outpatient or virtual clinics or phone calls. They included place of residence, function, mobility and bone-health status at time-points of 30 days, 6 weeks, 3, 4, 6 or 12 months. Only 11 publications followed patients past the 1 year time-point. One third of publications did not report data collection methods. Conclusion: Meta-analyses of results will provide estimates of mortality rates and other key hip fracture outcomes. Some long-term outcomes have been collected at most hospitals treating acute hip fracture in Ireland in the last 15 years. Qualitative research in needed to identify facilitators of follow-up to inform practice nationally.